Perancangan dan Implementasi Sistem Informasi Presensi Guru dan Tenaga Kependidikan Menggunakan Framework Codeigniter - Lesmideyarti, Dwi; Ihsan, Ihsan; Yanti, Nur; Armin, Armin (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Negeri Balikpapan, 2023)
The world of work, both from the level of government employees, BUMN employees, private company employees and others, is demanded to be able to adapt to technological advances. So that employee attendance can be easily monitored by superiors directly both when they come, when they go home and work location. This research activity is SMK Negeri 1 Balikpapan as a partner to implement a web server and website attendance information system for teachers, education staff and other employees. The problem faced by partners is that for employees working at SMK Negeri 1 Balikpapan attendance attendance only uses a fingerprint and retrieves data using a flash drive manually not integrated directly into the server automatically so that leaders cannot monitor and also when working outside the office cannot make attendance at at that moment. This research aims to help an easy system for teachers and education staff who are working outside the city with camera features and location points so they can take attendance. The results of this study are that it runs well without problems and can make it easier to recap the results of employee absences and reduce fraud that will be carried out in the absence of teachers and education staff at SMK Negeri 1 Balikpapan.